INOVASI ONIGIRI SEHAT DARI IKAN KEMBUNG SEBAGAI UPAYA PENCEGAHAN STUNTING: STUDI KASUS DI DESA KALIRANDUGEDE - Sujono, Rusny Istiqomah; Janah, Miftakhul; Ramadhan, Rizki; Nurpratiwi, Ela Dwi; Ngizzah, Nailul; Hermawan, Aris; Nurfaedah, Nurfaedah; Mutaqin, Fatih; Nurjanah, Siti; Fadhila, Nurma; Tirsardewi, Sartika; Ratnasari, Dwi; Emilda, Yufa (Universitas Mataram, 2024)
Stunting is a chronic nutritional problem that affects toddlers' growth, particularly when their height does not align with age standards. In Indonesia, the prevalence of stunting in 2022 was 21.6%, still above the WHO standard of 20%. In response, Alma Ata University, through the Real Work Lecture (KKN) Program, implemented a community-based intervention in Kalirandugede Village, Kendal, to reduce stunting rates. This program combines nutrition education and utilization of local potential with a participatory approach. One of the main activities is counseling on the importance of consuming animal protein, especially mackerel, which is rich in nutrition and affordable. Additionally, this program presents